2009
DOI: 10.1099/mic.0.028712-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of specific bacteria in wound biofilms using peptide nucleic acid fluorescent in situ hybridization (PNA FISH)

Abstract: Biofilms provide a reservoir of potentially infectious micro-organisms that are resistant to antimicrobial agents, and their importance in the failure of medical devices and chronic inflammatory conditions is increasingly being recognized. Particular research interest exists in the association of biofilms with wound infection and non-healing, i.e. chronic wounds. In this study, fluorescent in situ hybridization (FISH) was used in combination with confocal laser scanning microscopy (CLSM) to detect and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(144 citation statements)
references
References 31 publications
4
138
1
Order By: Relevance
“…Second, very few studies using these models have attempted to recapitulate the polymicrobial nature of wound infections. 10,39 Third, majority of these studies have been shortterm acute-phase studies that are insufficient by design to understand the long-term implications of biofilm-host interactions. Among small animals, the rabbit ear wound model seems promising.…”
Section: In Vivo Biofilm Modelsmentioning
confidence: 99%
“…Second, very few studies using these models have attempted to recapitulate the polymicrobial nature of wound infections. 10,39 Third, majority of these studies have been shortterm acute-phase studies that are insufficient by design to understand the long-term implications of biofilm-host interactions. Among small animals, the rabbit ear wound model seems promising.…”
Section: In Vivo Biofilm Modelsmentioning
confidence: 99%
“…10,19 Microbes in biofilms that otherwise may not be recovered utilizing standard culture techniques on agar may be identified with fluorescent in situ hybridization or other molecular based techniques. 20 …”
Section: Discussionmentioning
confidence: 99%
“…13,14,[20][21][22][23][24][25][26][27][28] Furthermore, it is likely that the presence of pathogenic biofilms substantially contribute to antimicrobial tolerance. Thus, identifying biofilms in wounds is a clinically important issue, particularly when a tissue biopsy specimen is not available.…”
Section: Relevant Basic Science Contextmentioning
confidence: 99%
“…Many stu di es in dica ted that FISH met hod can iden tify mic ro or ganisms with very high sen si ti vity (100%) and spe ci fi city (100%) and mi xed in fec ti ons can al so be de tec ted by this met hod. [22][23][24] Be si de this, ot her stu - Börekçi ve ark. Enfeksiyon Hastalıkları di es ha ve in di ca ted that PCR-EI A and se mi-nes ted PCR were mo re sen si ti ve than ro u ti ne phe noty pic met hods for the de tec ti on and iden ti fi ca ti on of mic ro or ga nisms in mi xed cul tu res.…”
Section: Discussionmentioning
confidence: 99%
“…21 Se ve ral stu di es ha ve shown that mix tu res of iso la tes in cul tu res can be de tec ted by FISH met hod and FISH is mo re sen siti ve than con ven ti o nal met hods in the de tec ti on of mix tu res of iso la tes in blo od cul tu res. [22][23][24] The aims of this study we re first to in ves ti gate the cli ni cal fe a tu res and risk fac tors in pa ti ents with sing le and mul tip le-spe ci es can di de mi a de tected by FISH met hod. In addition, the epi so des of bre akt hro ugh can di de mi a we re eva lu a ted.…”
Section: Gürol Emekdaşmentioning
confidence: 99%